Wrongful Convictions with Prison Sentences in Spain: Exoneree Characteristics, Crime Types, and Contributing Factors - Sánchez, Nuria; Blanco-Velasco, Guadalupe; Geven, Linda M.; Masip, Jaume; Manzanero, Antonio L. (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2024)
Researchers worldwide have extensively explored the factors contributing to wrongful convictions and the characteristics of individuals affected by these miscarriages of justice for over a century. Despite these global efforts, limited research has been conducted on this issue in Spain. This study seeks to address this gap. We trained coders to assess available review judgments issued by the Spanish Supreme Court from 1996 to 2022. We identified 89 cases of individuals wrongly sentenced to deprivation of liberty. Our findings indicated that 92% of those wrongfully convicted were male, with the majority having a prior criminal record. Most exonerations involved minor crimes, and 85% of individuals were sentenced to less than 4.5 years of deprivation of liberty. Professional misconduct emerged as the primary contributing factor, followed by the misapplication of forensic science, misidentifications, false testimonies, and false confessions. This project sheds light on wrongful convictions in Spain, emphasizing the need for comprehensive measures to address this issue. The current results have practical implications for justice professionals, policymakers, and legal practitioners. It is crucial to educate professionals in the judicial system on the causes of judicial errors, the biases that may influence them, and best practices to improve processes and reduce the occurrence of wrongful convictions.